The peruvian state and regional crises - the development of regional movements, 1968-1980 - Slater, David (2022)
This study is about the social movements of Latin America through which they were located in Peru, after his experience in Dar es Salaam (Tanzania) the author (Slater) introduces us to development studies from radical geography, it is the exploration of the power of peasant social movements, contrary to what most social scientists studied as labor movements from central countries. Having a postcolonial position from radical geography, it also explores the territorialities of the wage earners of the coastal cities and of the regional peasant movements of the interior of Peru, studying the contradictions of capital and wage labor and registering the non-wage labor that existed before the agrarian reform of the military government of Velasco Alvarado. I also record the “other” non-capitalist forms of production that persisted as alternative territorialities based on democracy, citizen participation and the struggle against the hegemonic and disorderly Peruvian capitalism, as well as identifying the gaps or errors of state intervention in the provincial territories from the hegemonic capital city. Peruvian of a military regime that declared itself revolutionary, which also did not dare to call it reformist. He focused on two social movements, one in the south of Peru in Arequipa and the other in the east of the country in Pucalpa.